Impact of Biochar Amendment on Soil Quality and Crop Yield in a Greenhouse Environment - Marzaioli, Rossana; Coppola, Elio; Iovieno, Paola; Pentangelo, Alfonso; Pane, Catello; Rutigliano, Flora Angela (Journal of Environmental Accounting and Management, 2026)
Greenhouse agriculture, a widespread practice in the Mediterranean basin, is prone to impoverishment in soil organic carbon because of crop removal and high decomposition rate. Open-field experimentation has shown that the addition of biochar, a product of thermochemical conversion of biomass, under a limited concentration of oxygen, increases the soil organic C pool, enhances crop productivity and improves C terrestrial sink. The present study investigates the effect of biochar amendment in a greenhouse environment in a Southern Italy organic farm. Two doses (10 or 20 t ha-1) of biochar from conifer pruning wastes were applied immediately before planting 1-week old plants of pepper (Capsicum annuum L.). Plant growth and crop yield were evaluated six months later, at the end of cultivation, in biochar-treated and in control (without biochar) plots. Soil samples were collected in the same plots immediately after biochar addition and six months later and were analyzed for the following parameters: bulk density, water- holding capacity, pH, electrical conductivity, organic carbon, mineral nitrogen, total microbial biomass and fungal mycelium contents, soil respiration, nitrogen mineralization, potential nitrification, soil suppressiveness to Rhizoctonia solani. A single biochar application caused no apparent damage to the crop; on the other hand, no improvement was observed in crop yield or soil suppressiveness to R. solani. In contrast, the single char application positively affected soil respiration, nitrogen mineralization and potential nitrification. These preliminary results suggest that soil amendment with biochar is a potentially useful practice in greenhouse agriculture, yet further experimentation is necessary to assess optimal amounts for better crop productivity and soil quality.